Farmers’ knowledge and management of potato late blight in Peruvian highlands: implications for an integrated disease management program - Pérez, W.; Arias, R.; Barreto, M.; Sanabria, K.; Andrade-Piedra, J.L. (2018)
Using a semi-structured questionnaire, 1198 Peruvian farmers were interviewed on their knowledge about late blight (LB) and its current management practices. Farmers overwhelmingly considered LB as the main foliar constraint in both potato growing areas. However, most farmers considered the interaction of a rainfall, sunny and foggy days as the cause of the disease and only few mentioned to a “fungi”. The main method to control LB is the use of fungicides, but some of them use insecticides, foliar fertilizers, hormones, and commercial leach. Commonly, the first fungicide spray is at plant emergence and then applications between 7 and 8 days. Fungicides based on cymoxanil and mancozeb were the most used in both areas, however, farmers mix until 5 pesticides at the same time. Over dosage or under dosage are common among farmers, which follow indications of pesticide sellers or use their own criteria. Farmers overwhelmingly no distinguished different levels of susceptibility among Peruvian potato varieties. To improve farmers’ capacities for better management of LB, is necessary to change pesticide-handling practices, promote the use of resistant varieties and use of other complementary control practices, through of an intensive, participatory training, which requires the support and involvement of key stakeholders, including agrochemicals companies, farmers, national and international R&D organizations, donors, governments, and NGOs.